The margin of error in opinion studies for the 2020 Bolivian general elections - Foronda Monasterios, Eddy Angel (2021)
In Bolivia there is a strong debate about the precision in the estimation of results disseminated by opinion studies on electoral matters, especially in the last general elections of the 2020 administration, essentially the pre-election polls that estimate the percentage of intention to vote of a candidate running for political authority. In this study, it was analyzed how pre-election surveys should be structured mainly in the part of the sample design, on the other hand, the results released by companies authorized to carry out these studies were analyzed, special emphasis was also placed on the margin of error that is a very important element in the dissemination of results. Likewise, the results of the last general elections 2020 were compared. Finally, the standard error of the valid vote for each candidate was estimated with the Boostrap resampling method using the free software R.